Improving patient safety awareness in nursing students through low-fidelity simulation and clinical practice: Pre-experimental study - Septa Meriana Lumbantoruan; Agustina Saputri; Juhdeliena Juhdeliena; Rani Sonia Wardani (Jurnal Keperawatan Padjadjaran, 2026)
Background: The incidence of patient harm is increasing globally, with nursing students contributing to errors during training and clinical practice. However, research on nursing students’ awareness of patient safety following simulation-based training and clinical practice remains limited. Purpose: This study analysed nursing students’ awareness of patient safety before and after low-fidelity simulations and clinical practice. Method: A one-group pretest–post-test interventional design was used. The study involved 446 first-year nursing students at Universitas Pelita Harapan, Tangerang, Indonesia. The independent variable was participation in structured low-fidelity simulation sessions followed by clinical practice, while the dependent variable was patient safety awareness. Awareness was measured before and after the intervention using the World Health Organization Patient Safety Questionnaire, consisting of 33 items rated on a five-point Likert scale. It contains five domains: knowledge of patient safety, safety of the healthcare system, ability to influence patient safety, personal attitudes toward patient safety, and workplace safety. Data were analysed using descriptive statistics and paired-samples t-tests with a significance level of 0.05. Results: Total patient safety awareness scores increased significantly after the intervention (118.25 ± 9.90 vs. 120.78 ± 10.76, t = -4.90, p < 0.001). Significant improvements were observed in knowledge of patient safety, perception of healthcare system safety, and perceived ability to influence safety. Students with a science background in senior high school demonstrated higher awareness. Conclusion: Low-fidelity simulation and clinical practice significantly improved nursing students’ patient safety awareness, supporting early integration of structured patient safety education in nursing curricula.